Validation of the SCORE2 risk prediction algorithm in a Portuguese population: A new model to estimate 10-year cardiovascular disease incidence in Europe - Temtem, Margarida; Mendonça, Maria Isabel; Santos, Marina; Sá, Débora; Sousa, Francisco; Freitas, Sónia; Borges, Sofia; Henriques, Eva; Rodrigues, Mariana; Soares, Carolina; Rodrigues, Ricardo; Serrão, Marco; et al. (Revista portuguesa de cardiologia, 2024)
Subjects without cardiovascular (CV) disease (CVD) may suffer from subclinical atherosclerosis, and are at increased risk for atherosclerotic CV events (ASCVE). The ESC/EAS risk SCORE was updated by SCORE2, which estimates 10-year risk of fatal and non-fatal CVD in European populations aged 40–69 years without established CVD or diabetes. Our aim was to compare the two ESC/EAS risk scores and to validate SCORE2 in our population. A total of 1071 individuals (age 57.2±6.1 years; 75.2% male) without CVD or diabetes, from GENEMACOR study controls, were analyzed over 5.4±3.9 years. The population was stratified into risk categories according to the two scores, and the area under the ROC curve (AUC) and Harrell's C-index assessed the scores’ performance. Calibration was performed using the goodness-of-fit test, and occurrence of the first event assessed by Cox regression. Kaplan–Meier analysis estimated SCORE2 survival. SCORE stratified subjects into four risk categories: low (7.4%), moderate (46.5%), high (25.3%) and very high (20.8%), and SCORE2 into three: low-to-moderate (24.7%), high (59.0%) and very high (16.2%). SCORE presented good discrimination for CV mortality (AUC=0.838; C-index=0.834, 95% CI: 0.728–0.940), as did SCORE2 for total CV events (AUC=0.744; C-index=0.728, 95% CI: 0.648–0.808). Calibration did not show a disparity between observed and expected ASCVE. The probability of ASCVE was eight times higher in very-high-risk SCORE2 (p=0.001), and three times in the high-risk group (p=0.049). Event-free survival was 99%, 90% and 72% in the low-to-moderate, high and very-high-risk categories, respectively (p<0.0001). SCORE2 improved population stratification by identifying higher-risk patients, enabling early preventive measures. It showed good discriminative ability for all ASCVE. Indivíduos sem doença cardiovascular (DCV) sintomática podem sofrer de aterosclerose subclínica tendo risco de eventos cardiovasculares (ECV). O SCORE Europeu foi atualizado pelo SCORE2 que estima o risco de DCV fatal e não fatal a 10 anos, nos europeus entre 40 e 69 anos, sem DCV ou diabetes. O objetivo é comparar estes dois scores de risco, validando o SCORE2 na nossa população. 1071 indivíduos (57,2 ± 6,1anos; 75,2% sexo masculino), sem DCV ou diabetes, foram seguidos durante 5,4 ± 3,9 anos e estratificados em categorias de risco. O poder discriminativo dos scores para ECV foi estimado pela área abaixo da curva ROC (AUC) e pelo índice C de Harrell. A calibração foi avaliada pelo Hosmer-Lemeshow; o risco de ocorrência do 1.° evento pela regressão de Cox. Kaplan-Meier estimou a sobrevivência do SCORE2. O SCORE estratificou em quatro categorias de risco, baixo (7,4%), moderado (46,5%), alto (25,3%) e muito alto (20,8%) e o SCORE2 em três, baixo-a-moderado (24,7%), alto (59,0%) e muito alto (16,2%). O SCORE apresentou boa discriminação para mortalidade CV (AUC = 0,838; índiceC = 0,834) e o SCORE2 discriminou para a totalidade dos ECV (AUC = 0,744; índiceC = 0,728). A calibração foi adequada. A probabilidade de ECV aumentou oito vezes na categoria de muito alto risco (p = 0,001) e três vezes na de alto risco (p = 0,049). A sobrevivência livre de eventos foi 99%, 90% e 72% nas categorias de baixo-a-moderado, alto e muito alto risco, respetivamente (p < 0,0001). O SCORE2 melhorou a estratificação ao identificar indivíduos de maior risco, permitindo medidas preventivas precocemente. Mostrou boa capacidade discriminativa para ECV.